Predictors of rethrombosis and death in patients with COVID-19 after lower limb arterial thrombectomy for acute ischemia - M. V. Afonkina; O. Yu. Martynova; S. S. Nazarova; A. V. Korotkikh; O. V. Lebedev; S. V. Artyukhov; O. Sh. Mukhtorov; R. Yu. Lider; Sh. Van; T. Sh. Ramazanova; L. V. Roshkovskaya; A. S. Zharova; et al. (Российский кардиологический журнал)
Aim. To identify predictors of rethrombosis and death in patients with coronavirus disease (COVID-19) after thrombectomy for acute lower limb ischemia.Material and methods. For the period from April 2020 to January 2022, 189 pa tients with acute arterial lower limb thrombosis and acute lower limb ischemia were included in this study. In all cases, a positive polymerase chain reaction test for SARS-CoV-2 was obtained. According to chest multislice computed tomography, bilateral multisegmental pneumonia was identified as follows: 76 patients — grade 2 (25-50% of lung tissue involvement); 52 patients — grade 3 (50-75%); 61 patients — grade 4 (>75%). Breathing was carried out as follows: in 88 patients — spontaneous; in 42 — with oxygen administration by nasal cannula; 26 — non-invasive ventilation; 33 had artificial ventilation. All acute arterial thromboses developed within the hospital at 4,5±1,5 days after hospitalization. The time between the onset to diagnosis verification was 27,8±5,0 min. The revascularization strategy was established by a multidisciplinary team meeting. The interval between the development of acute ischemia symptoms and surgery was 45,9±6,3 minutes. Thrombectomy was performed according to the standard technique, under local and/or intravenous anesthesia, using 3F-7F Fogarty catheters.Results. Retrombosis developed in 80,4% of cases 6,4±5,1 hours after surgery. In 59,8% of cases, retrombectomy turned out to be ineffective and the patient underwent limb amputation. In 65,6% of patients, a death was established due to multiple organ dysfunction. Among them, limb amputation was performed in 103 patients. Binary logistic regression identified following predictors of retrombosis/ death: age over 70 years (odds ratio (OR), 30,73; 95% confidence interval (CI), 11,52-33,7), obesity (OR, 15,53; 95% CI, 6,41-78,19), diabetes (OR 14,21; 95% CI, 5,86-49,21), vasopressor support (OR 8,55; 95% CI, 4,94-17,93), mechanical ventilation (OR 7,39; 95% CI, 4,81-16,52).Conclusion. Predictors of retrombosis and death in patients with COVID-19 after lower limb arterial thrombectomy are age over 70 years, obesity, diabetes, vasopressor support, and mechanical ventilation.